The testimony of St. Paul to Christ viewed in some of its aspects - Knowling, Richard John (C. Scribner's sons, 1905)
1st ser. 1903: The documents.--2d ser. 1904: St. Paul's testimony in relation to the Gospels.--3d ser. 1905: St. Paul's testimony in relation to the life of the church.